Design orientation in new product development and its measurement. Issue 1 (4th December 2019) - Cantó, Mónica; Frasquet, Marta; Irene, Gil-Saura
Abstract : Purpose: The purpose of this paper is to define the design orientation construct, proposing a theoretical framework for its analysis and a validated tool for its measurement. Design/methodology/approach: The process of scale development follows the recommendations of DeVellis (1991). After qualitative research with experts, quantitative research was performed on a sample of 209 SMEs in the furniture and lighting sectors. The results, based on the use of the confirmatory factor analysis technique, yielded a measurement scale with solid psychometric properties, thus confirming its reliability and validity. Findings: The resulting scale comprised 19 items grouped into seven dimensions: awareness of the benefits of design, design sensibility, basic design skills, specialized design skills, involving others, design organization and innovation skills. Practical implications: The instrument can be used to quantify the degree of design orientation in a company, thus enabling cross-sectional and longitudinal diagnoses. Originality/value: By operationalizing the design orientation construct, this scale serves as a starting point for future developments in the field of business design and design management.